Allopatric and sympatric diversification within roach (Rutilus rutilus) of large pre‐alpine lakes. (19th September 2019) - Rieder, Jessica M.; Vonlanthen, Pascal; Seehausen, Ole; Lucek, Kay
Abstract: Intraspecific differentiation in response to divergent natural selection between environments is a common phenomenon in some northern freshwater fishes, especially salmonids and stickleback. Understanding why these taxa diversify and undergo adaptive radiations while most other fish species in the same environments do not, remains an open question. The possibility for intraspecific diversification has rarely been evaluated for most northern freshwater fish species. Here, we assess the potential for intraspecific differentiation between and within lake populations of roach ( Rutilus rutilus )—a widespread and abundant cyprinid species—in lakes in which salmonids have evolved endemic adaptive radiations. Based on more than 3, 000 polymorphic RADseq markers, we detected low but significant genetic differentiation between roach populations of two ultraoligotrophic lakes and between these and populations from other lakes. This, together with differentiation in head morphology and stable isotope signatures, suggests evolutionary and ecological differentiation among some of our studied populations. Next, we tested for intralacustrine diversification of roach within Lake Brienz, the most pristine lake surveyed in this study. We found significant phenotypic evidence for ecological intralacustrine differentiation between roach caught over a muddy substrate and those caught over a rocky substrate. However, evidence for intralacustrine genetic differentiation is at best subtle and phenotypic changes may therefore be mostly plastic. Overall, our findings suggest roach can differ between ecologically distinct lakes, but the extent of intralacustrine ecological differentiation is weak, which contrasts with the strong differentiation among endemic species of whitefish in the same lakes. Abstract : Intraspecific differentiation in response to divergent natural selection between environments is a common phenomenon in some northern freshwater fishes. Understanding why these taxa diversify and undergo adaptive radiations while most other fish species in the same environments do not, remains an open question. Here, we assess the potential for intraspecific differentiation between and within lake populations of roach (Rutilus rutilus)—a widespread and abundant cyprinid species—in lakes in which salmonids have evolved endemic adaptive radiations.